Estimation of compressive strength of concrete structures using the ultrasonic pulse velocity method and spectral analysis of surface wave method. (May 2015) - Hong, S. U.; Cho, Y. S.; Kim, S. H.; Lee, Y. T.
Abstract : This research focuses on the non-destructive test method, which is helpful in renovating old buildings without destructing concrete structure, thus estimating compressive strength of the concrete structure is of increasing importance. This paper utilises the ultrasonic pulse velocity method and the spectral analysis of surface wave method to estimate the compressive strength. The relationship between the test results using the two methods and compressive strength of concrete is analysed, respectively. The correlation between the ultrasonic pulse velocity and compressive strength of concrete is V p = 2178·7 F ck 0·1949, and the relative error range is 4·37%. The correlation between the surface wave velocity and compressive strength of concrete is V R = 902·41, F ck 0·2487, and the relative error range is 6·07%. Regression analysis shows that the correlation between the ultrasonic pulse velocity and surface wave velocity is V R = 0 · 8635 V P - 1562, and the relative error range is 2·57%. Multiplexing of the ultrasonic pulse velocity and surface wave velocity is used to derive F ck = 60·07 V P - 31·24 V R - 157·69, and the relative error range is 3·17%. It is found that concrete compressive strength and velocities of the two methods have a close correlation.